Correlation of the Changes of Gray Matter Volume with Aβ Deposition and Learning and Memory Abilities in APP/PS1 Mice at Different Periods - Yuhao ZHANG; Hao JIN; Xiufeng ZHANG; Shengxiang LIANG; Weilin LIU; Jing TAO; Lidian CHEN (康复学报)
Objective:To analyze the correlation in the changes of cerebral gray matter volume and the ability of memory learning, and the deposition of β-amyloid protein (Aβ) in related brain regions of Alzheimer's disease (AD) double-transgenic APP/PS1 model mice, which is expected to provide reliable behavioral and imaging basis for probing the pathological features of AD animal models.Methods:A total of two groups mice were included in this study, including the wild type (WT) group and the APP/PS1 group, with 36 mice in each group. The C57-BL/6 mice were selected in the WT group, and APP/PS1 double transgenic mice were selected in the APP/PS1 group. The two groups were composed of mice of different ages of 2,6, and 12 months respectively, with 12 mice of each month in each group. The Morris water maze test (including location navigation test and spatial exploration test) was used to detect the spatial memory learning ability and spatial memory extraction ability of the two groups of mice, and the magnetic resonance T2-weighted imaging (MRI T2WI) scan was used to detect the changes of gray matter volume in the bilateral entorhinal cortex and hippocampus of mice. The brain paraffin sections of two groups of mice of different months were separated and prepared, and the Aβ deposition in bilateral entorhinal cortex and hippocampus of the two groups was detected by Thioflavine-s fluorescence staining, and the correlation between the changes of gray matter volume and memory learning ability and Aβ deposition in the corresponding brain area of the two groups was analyzed by Pearson correlation analysis.Results:①The results of Morris water maze test: compared with the WT group, there was no significant difference in the behavioral results of the 2-month-old mice in the APP/PS1 group, and the difference was not statistically significant (P>0.05); the escape latency of mice of the APP/PS1 group at the 6 and 12 month-old increased significantly, the number of crossing platforms of the APP/PS1 group at the 6 and 12 month-old decreased significantly, and the difference was statistically significant (P<0.05).②The results of MRI T2WI scan: compared with the WT group, there was no significant change in the gray matter volume of the APP/PS1 group at 2-month-old, and the difference was not statistically significant (P>0.05); the volume of the entorhinal cortex of the APP/PS1 group at 6-month-old decreased significantly, and the volume of the entorhinal cortex and hippocampus of the APP/PS1 group at 12-month-old mice decreased significantly, the difference was statistically significant (P<0.05).③The results of Th-s fluorescence staining test: Aβ deposition was not detected in WT group and APP/PS1 group at 2-month-old; compared with the WT group, a small amount of Aβ deposition could be detected in the entorhinal cortex and hippocampus of the APP/PS1 group at 6-month-old, while a large number of dense Aβ plaques can be detected in the entorhinal cortex and hippocampus of the APP/PS1 group at 12-month-old.④Correlation analysis results: APP/PS1 group mice's entorhinal cortex and hippocampus volume changes were significantly negatively correlated with escape latency (r=-0.729, P<0.001; r=-0.643, P<0.001); the volume changes of the entorhinal cortex and hippocampus in the APP/PS1 group showed a positive correlation with the number of crossing platforms (r=0.705, P<0.001; r=0.719, P<0.001); the volume changes of the entorhinal cortex and hippocampus in the APP/PS1 group were significantly negatively correlated with Aβ deposition (r=-0.865, P<0.001; r=-0.885, P<0.001).Conclusion:APP/PS1 transgenic mice may have learning and memory dysfunction at 6-month-old, and it gradually worsen with time; the learning and memory dysfunction may be related to the atrophy of the entorhinal cortex and hippocampus in the brain of mice, and excessive Aβ deposition may be the one of the factors that cause the brain gray matter volume to shrink.